Lactic Acid Bacteria as Biopreservation Against Spoilage Molds in Dairy Products – A Review - Shi, Ce; Maktabdar, Maryam (Frontiers in Microbiology, 2022)
Mold spoilage of dairy products such as yoghurt is a concern in dairy industry. Not only does it lead to substantial food waste, economic losses, and even brand image damage, but it may also cause public health concern due to the potential production of mycotoxin. Good hygiene practices are necessary to prevent contamination, but contamination may nevertheless occur at the production site and, not least, at the site of the consumer. In recent years, there has been a growing interest from consumers for “clean label” food products, which are natural, less-processed, and free of added, chemical preservatives, and a wish for shelf lives of considerable length in order to minimize food waste. This has sparked an interest in using lactic acid bacteria (LAB) or their metabolites as biopreservatives as a way to limit the growth of spoilage organisms in dairy products. A range of compounds produced by LAB with potential antifungal activity have been described as contributing factors to the inhibitory effect of LAB. More recently, growth inhibition effects caused by specific competitive exclusion have been elucidated. It has also become clear that the sensitivity towards both individual antifungal compounds and competition mechanisms differ among molds. In this review, the main spoilage molds encountered in dairy products are introduced, and an overview of the antifungal activity of LAB against different spoilage molds is presented including the main antifungal compounds derived from LAB cultures and the sensitivity of the spoilage molds observed towards these compounds. The recent findings of the role of competitive exclusion with emphasis on manganese depletion and the possible implications of this for biopreservation are described. Finally, some of the knowledge gaps, future challenges, and trends in the application of LAB biopreservation in dairy products are discussed.